An investigation into the roles of the Katakana syllabary in Japanese discourse: From the perspective of discourse producers' motivation. Issue 2 (3rd July 2019) - Cochrane, Yumiko
ABSTRACT: This article investigates the role(s) of the katakana syllabary in Japanese discourse, with a focus on the discourse producer's underlying motivation for using katakana for native Japanese terms and how it influences word perception. Specifically, this study analyses 1) a corpus of texts to identify patterns in use and 2) a survey of professional writers (e.g., journalists, column writers) to triangulate results obtained from text analysis. Results show that the katakana syllabary is used to indicate the word in question is somehow 'different' from the norm, making a visual and mental distinction in the commonly shared word or concept. While each writer's motivations may widely vary, the findings of this study suggest that in any written discourse, katakana may be employed to conceptualise a dichotomous view in otherwise common concepts. This also suggests that over time the original role of the katakana syllabary has been extended to becoming the linguistic choice of convenience, with roles ranging from filling lexical gaps to creating meaning gaps in Japanese native words.